Progress in understanding and utilizing TNF-α inhibition for the treatment of psoriatic arthritis. (3rd March 2016) - Caso, Francesco; Lubrano, Ennio; Del Puente, Antonio; Caso, Paolo; Peluso, Rosario; Foglia, Francesca; Benigno, Carolina; Girolimetto, Nicolò; Bottiglieri, Paolo; Scarpa, Raffaele; Costa, Luisa
ABSTRACT: The improved recognition of pathogenetic molecular mechanisms has led to the use of drugs targeting cytokines in different inflammatory arthropathies as well psoriatic arthritis (PsA). In particular, the progress in knowledge on tumor necrosis factor (TNF)-α in the pathogenesis of PsA has changed the therapeutic approach by use of direct and receptor cytokine antagonists. Currently, infliximab (IFX), adalimumab, etanercept, golimumab and certolizumab pegol represent the five anti-TNF-α available for the treatment of PsA. This review describes evidence on treatment aimed at neutralizing TNF-α in PsA patients, from the first study in 2000 until today, mainly derived from randomized clinical trials. In comparison with traditional therapies, anti-TNF-α agents have shown to have more efficacy both in treating clinical aspects, including enthesitis, dactylitis, joint pain and swelling, axial involvement, nail and skin lesions, and in reducing radiographic progression. Moreover, anti-TNF-α agents have been demonstrated to be reasonably safe in PsA, as confirmed by data derived by different registries.